Bioremediation of Hydrocarbon: a mini review - Mohd Khalizan Sabullah; Hartinie Marbawi; Ainol Azifa Mohd Faik; Rahmath Abdulla; Suraya Abd Sani; Feodora Grace Japanis Japanis; J. Niranjana Jaganathan; Mark Wilson Julius; Nurshafiqah Saini; Reverend Roland (hibiscus publisher, 2018)
Several contaminant that present in the river able to be removed through the physical and chemical approach. However, the efficiency is still low especially to remediate the dissolved compound such pesticides, drug and heavy metal. Nowadays, river rehabilitation using a biological approach known as bioremediation gets a great attention as the treatment processes are environmentally friendly, low cost, easily to handle and portable. Moreover, the result is highly satisfactory and at the same time no cause harm to the society. This mini-review highlights the introduction application of bioremediation to clean the contaminated environment, especially river. The advantages and disadvantages were also will be discussed